Analisis dan Perancangan Sistem Informasi Penggajian Karyawan Berbasis WEB pada PT. Batam Bintan Telekomunikasi Lagoi - Nanny Raras Setyoningrum; Danil Syah Arihardjo (Program Studi Informatika Universitas Teknologi Sumbawa, 2021)
The payroll system is an important thing in a company. Salary is one of the important things that encourages employee performance so that the company continues to run well. PT. Batam Bintan Telecommunications Lagoi Service Operations in the calculation of salaries still manually only use MS.Excel and pay slips are still manually in the form of a salary slip to be submitted to employees. This makes work in the finance department slow, and employees cannot get information about overtime income. The purpose of this study is to design an information system to facilitate the performance of salary management. With a SWOT analysis, it was found that the factors that cause problems in the current payroll system at PT. Batam Bintan Telecommunications Lagoi Service Operations, and solutions were found to solve or minimize problems with the current payroll system. The method in this research is divided into two stages, namely the data interview method with observation and interviews and the software development method using the Waterfall model. Website-based payroll information system is created using the Laravel Framework using the PHP programming language, and MySQL as its database. With a web-based payroll system can help calculate salaries automatically and systematically, as well as quickly and accurately. Thus, employee performance is better and the company gets the benefits too.